Adoption of Public Library 2.0: Librarians’ and teens’ perspective - Abidin, M. Ismail; K., Kiran; A., Abrizah (Malaysian Journal of Library and Information Science, 2017)
Abidin, M. I., Kiran, K., & Abrizah, A. (2013). Adoption of Public Library 2.0: Librarians’ and teens’ perspective. Malaysian Journal of Library & Information Science, Vol.18, no. 3: 75-90. This paper addresses the adoption of Public Library 2.0 from the perspective of Malaysian librarians and library users, particularly the teenagers. Qualitative approach, using content analysis of fourteen state public library websites and interviews with librarians, was applied to explore the level of Web 2.0 adoption, and to ascertain the motivation and purpose of adopting these technologies. Quantitative approach was used to obtain user perspective on the use of Web 2.0 by public libraries. Findings reveal that the National Library of Malaysia (PNM), leads in terms of total number of Web 2.0 tools deployed. Social networking applications (specifically Facebook and Twitter) are the most used in Malaysian public libraries. The main purpose of using Web 2.0 tools is to provide information on library activities, news and announcement. The adoption of Web 2.0 applications is not guided by any definite policies and there is a lack of monitoring of the librarians and users activities on the social media. No innovative use of Web 2.0 tools was discovered to enhance the participation of the library community, especially targeted for teens.Teenagers are receptive towards use of Public Library 2.0, but their lack of the knowledge on how Web 2.0 tools can improve their interaction with the library services, limits their ability to give feedback on their expectations. The evidences point to a dire need for immediate improvements in the management of Web 2.0 based library services.